New realities of the administrative-territorial structure of Ukraine and areas of ethnic minorities’ settlement: Geographical correlations and social consequences - Miroslav Dnistryanskyi; Мирослав Дністрянський; Dnyisztrjanszkij Miroszlav; Молнар Йосип; Molnár József; Nataliya Dnistryanska; Наталія Дністрянська; Stefan Molnar D.; Molnár D. István; Молнар Д. Стефан (HUN-REN Research Centre for Astronomy and Earth Sciences, 2024)
Abstract. This article analyses the ethno-geographical problems of the reformed system of administrative and territorial structure of Ukraine. The authors consider the alignment of newly created administrative units (rayons, territorial communities) and areas of compact settlement of ethnic minorities as a favourable prerequisite for the organisation of local self-government and the establishment of balanced and mutually beneficial ethno-political relations in the state. The analysis of the ethno-geographical parameters of ethnic minorities and the configuration of the newly created administrative-territorial units revealed that the population of ethnic minorities in Zakarpattia, Chernivtsi and Odesa oblasts was given the opportunity to organise territorial communities in which they constitute the majority. At the same time, studies have shown that it was not easy to implement this approach in the newly created administrative districts, given the officially defined criteria, the politicisation of the issue and the relatively high degree of mosaic settlement of ethnic groups. Therefore, the ethno-geographical factor was only partially taken into account in the formation of new administrative districts and the selection of district centres.
Examples of Zakarpattia, Chernivtsi and Odesa oblasts
Keywords: administrative and territorial reform; ethnic minorities; settlements; local self-government; territorial communities; Ukraine